The Effect of Paylater Payment Method Used in Online Impulsive Buying in Batam City - Fendy Cuandra (SEIKO : Journal of Management & Business, 2022)
Shopping sites or online buying and selling applications are growing and diverse due to advances in systems and technology. More and more types and methods of payment are being offered, one of which is Paylater. This study aims to discuss and deepen the analysis of the factors of the paylater by testing the effect on the impulsive buying of online consumers in Batam City. This study also analyzes the factors, namely Perceived Usefulness, Perceived Ease of Use, and Perceived Security that can affect the intention to use the paylater. The research data was collected through a questionnaire filled out by 206 respondents who used the paylater and processed using the SmartPLS 3. The results of the data processing and analysis conducted showed that there was a significant effect on the relationship between perceived usefulness and perceived security of intention to use paylater but perceived ease of use did not have the same relationship with intention to use the paylater. The results of this study also showed a significant relationship between the intention to use paylater to online impulsive buying in Batam City.